A study on the effectiveness of promotional tools used by the Katerina Hotel / Norhidayah Mohd Sehat (Faculty of Business and Management, 2007)
The research of "A Study on the Effectiveness of Promotional Tools Used by the Katerina Hotel" was conducted with three objectives which are first to determine the effectiveness of the existing promotional tools used by the Katerina Hotel, second to study the level of customer awareness towards the promotional activities done by the Katerina Hotel, and third to recommend the aspects that need to be improved to make the promotion strategies used become more effective. According to the Operation Manager of the Katerina Hotel, Mr. Rosli Bin Selamin in the year 2006, although the Katerina Hotel had implemented several promotion tools to increase the sales, the hotel was still unable to reach its target sales at RM 7 million per year (Figure 1.1) as it is suppose to be. This might be due to the promotional tools, which is not being implemented effectively besides the management does not utilize 100% all the promotional tools that they have (Figure 1.2). For the purpose of the study, descriptive research design had been adopted. The respondents of this study were customers that staying at the Katerina Hotel. 50 questionnaires had been distributed to those customers who recently stay at the hotel. The researcher had used stratified convenience sampling as the sampling technique. In this study, descriptive statistics had been used to interpret the data such as reliability testing, frequency tables. From the findings, the most effective promotional tools that the Katerina hotel should implement are sales promotions and advertising. For advertising, most of the respondents choose that advertising must be creative and attractive to attract the readers to try meanwhile for sales promotion, it is effective if the price being charged reasonable. Respondents also agreed it is effective that information and message can be easily reached target customer by having two-way communication and felt that internet is more effective for direct marketing. Results also showed most of the respondents are aware of the Katerina Hotel, but still the management not able reached target sales. This might due to other reasons besides promotion being done. This research also recommend some aspects that needs to be improved in order to make the promotional tools more effective and able to reach target sales in the future which are choose the right media, frequent doing the promotional activities, continuous promoting, reached target customers and able to make the readers to purchase.